Differences in Physical Activity and Sedentary Behavior Patterns of Postmenopausal Women With Normal vs. Low Total Hip Bone Mineral Density - Chopra, Swati; Morrow, Melissa M.; Ngufor, Che; Fortune, Emma (Frontiers in Sports and Active Living, 2020)
Purpose: Recent evidence suggests that sedentary behavior (SB) may be associated with bone health. This study compares free-living physical activity (PA) and SB distribution patterns of postmenopausal women with normal vs. low total hip bone mineral density (BMD). Methods: Sixty nine post-menopausal women [mean (min-max) age: 61 (46–79) years] wore ActiGraph GT3X+ activity monitors on the bilateral ankles for 7 days in free-living. Participants were split into two groups: those with normal hip BMD (T-scores ≥-1.0; N = 34) and those with low hip BMD (T-scores <-1.0; N = 35) as defined by the World Health Organization. Daily active time, step counts, sedentary time, sedentary break number, and median sedentary bout length were estimated from ankle acceleration data. The distribution and accumulation patterns of time spent in sedentary bouts, sedentary breaks, and stepping bouts, and sedentary break and stepping bout lengths' variability were also investigated. Group differences were assessed using two-sampled t-tests and Mann-Whitney U-tests with significance levels of 0.5. Results: Significant between group differences (p < 0.05) were in total daily active time [median (IQR): 257 (209–326) vs. 249 (199–299) min], step count [14,188 (10,938–18,646) vs. 13,204 (10,337–16,630) steps], sedentary time [669 (584–731) vs. 687 (615–753) min], and sedentary break number [93 (68–129) breaks vs. 88 (64–113) breaks], as well as median sedentary bout length [15.1 (11.9–22.1) vs. 15.8 (12.1–24.9) min]. Participants' sedentary bouts were found to be power law distributed with 52% of sedentary time occurring in bouts ≥20 min for the normal BMD group, and 58% for the low BMD group. Significant differences were observed between groups in sedentary bouts' and sedentary breaks' power distribution exponents (p < 0.0001) and patterns of sedentary and stepping time accumulation using the Gini index (p ≤ 0.0014). Variability was significantly lower for sedentary break and stepping bout lengths for the low BMD group (p ≤ 0.0001). Participants with lower hip BMD have longer sedentary bouts with shorter and less complex activity bouts compared to participants with normal hip BMD. Conclusion: The results suggest healthier hip BMD may be associated with PA distributed more evenly throughout the day with shorter sedentary bouts. PA distribution should be considered in exercise-based bone health management programs.